Neutron-capture elements record the ordered chemical evolution of the disc over time. Issue 4 (12th May 2022) - Horta, Danny; Ness, Melissa K; Rybizki, Jan; Schiavon, Ricardo P; Buder, Sven
ABSTRACT: An ensemble of chemical abundances probing different nucleosynthetic channels can be leveraged to build a comprehensive understanding of the chemical and structural evolution of the Galaxy. Using GALAH DR3 data, we seek to trace the enrichment by the supernovae Ia, supernovae II, asymptotic giant branch stars, and neutron-star mergers and/or collapsars nucleosynthetic sources by studying the [Fe/H], [α/Fe], [Ba/Fe], and [Eu/Fe] chemical compositions of ∼50 000 red giant stars, respectively. Employing small [Fe/H]–[α/Fe] cells, which serve as an effective reference-frame of supernovae contributions, we characterize the abundance-age profiles for [Ba/Fe] and [Eu/Fe]. Our results disclose that these age–abundance relations vary across the [Fe/H]–[α/Fe] plane. Within cells, we find negative age–[Ba/Fe] relations and flat age–[Eu/Fe] relations. Across cells, we see the slope of the age–[Ba/Fe] relations evolve smoothly and the [Eu/Fe] relations vary in amplitude. We subsequently model our empirical findings in a theoretical setting using the flexible Chempy Galactic chemical evolution (GCE) code, using the mean [Fe/H], [Mg/Fe], [Ba/Fe], and age values for stellar populations binned in [Fe/H], [Mg/Fe], and age space. We find that within a one-zone framework, an ensemble of GCE model parameters vary to explain the data. Using present day orbits from Gaia EDR3 measurements we infer that the GCE model parameters, which set the observed chemical abundance distributions, vary systematically across mean orbital radii. Under our modelling assumptions, the observed chemical abundances are consistent with a small gradient in the high-mass end of the initial mass function (IMF) across the disc, where the IMF is more top heavy towards the inner disc and more bottom heavy in the outer disc.